2001
DOI: 10.1148/radiol.2213010308
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Copy Mammographic Readings with Different Computer-assisted Detection Cuing Environments: Preliminary Findings

Abstract: CAD systems have the potential to significantly improve diagnostic performance in mammography. However, poorly performing schemes could adversely affect observer performance in both cued and noncued areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 32 publications
5
61
0
2
Order By: Relevance
“…An unexpected finding is the association between use of CAD and degraded sensitivity of readers for comparatively difficult cases; particularly striking because this affected the highly discriminating readers. This finding is, however, consistent with our aforementioned empirical study (16,17) and the study by Zheng et al (18), which strongly suggested that readers using CAD were biased by incorrect computer outputs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An unexpected finding is the association between use of CAD and degraded sensitivity of readers for comparatively difficult cases; particularly striking because this affected the highly discriminating readers. This finding is, however, consistent with our aforementioned empirical study (16,17) and the study by Zheng et al (18), which strongly suggested that readers using CAD were biased by incorrect computer outputs.…”
Section: Discussionsupporting
confidence: 93%
“…We also conducted two supplementary studies (16,17) with a set of cases selected to have large proportions of cancers incorrectly prompted by CAD. In these studies, radiologists proved significantly less sensitive with CAD than without, suggesting that incorrect CAD prompts may hinder readers under some circumstances, which is consistent with the findings of Zheng et al (18). Our further analyses of data from (6) suggested that CAD reduced radiologists' sensitivity in decisions about the more difficult cases -most of which were incorrectly prompted by the CAD tool -and increased sensitivity for comparatively easy cases (16).…”
Section: Cancer Screening and Previous Studies Of Cadsupporting
confidence: 88%
“…Zheng et al [31] have shown the impact of CAD sensitivity and false positive rate on radiologist performance with the four combinations of a CAD system with sensitivities of 90% or 50% and false positive rates of two or eight marks per four-image mammogram case (multiplying their per image false positive rates by 4). Their results showed that a CAD system with 90% sensitivity and two false positives per case improved radiologist performance, a CAD system with 90% sensitivity and eight false positives per case or a CAD system with 50% sensitivity and two false positives per case had no significant impact on radiologist performance, while a CAD system with 50% sensitivity and eight false positives per case was detrimental to radiologist performance.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the difference in performance. "Highly performing" CAD was shown to improve radiologists' performance, while "poor performing" CAD negatively affected their performance [6]. This shows how important designing a highly performing CAD system is.…”
Section: Introductionmentioning
confidence: 95%